Well-being, Trust and Society (Lebenswelt. Aesthetics and philosophy of experience., 2019)
The concept of well-being is correlated with social indicators linked in turn with the classical notion of “the good life”. The paper, instead, emphasizes the importance of relational aspects. It develops a reflection on the dialectic of interpersonal and systemic trust and mistrust, and it analyzes different semantic nuances of the notion of trust. A society characterized by well-being evidences strong type agency, a society with low levels of well being evidences weak type agency. Trust is a social resource indispensable for sustaining agency, society’s self-transformation and well-being. While trust is traditionally thought to contribute to social cohesion, mistrusting the rulers can also be considered a positive countervailing force in contemporary democracies. At the same time, the distrust sedimented in time creates, on the one hand, a saving expectation and on the other, paternalisation as a search for a substitute trust.
Keywords: Trust, Mistrust, Well-being, Social Cohesion